DENTAL IMPLANT CRITERIA BEFORE AND AFTER PLACEMENT WITH PANORAMIC RADIOGRAPHY: KRITERIA DENTAL IMPLAN SEBELUM DAN SESUDAH PENEMPATAN DENGAN GAMBARAN RADIOGRAFI PANORAMIK - Barunawaty Yunus (Dentika: Dental Journal, 2010)
The increasing demand towards dental implant in society with intermediate until high socio-economic status has forced implant practitioners to be more professional to work. This study aimed to find the differences between dental implant placement location before and after the dental implant examination by using the panoramic radiography. This research was a “Quasi Experimental” design with “Pre-Post Test”. This study was conducted in the RSGMP FKG UNHAS with the subject of treatment by the number of 30 samples, included both male and female, aged 20-50 years, losing 1-2 dental units, had no systemic diseases, no proximal caries , minimum jawbone was 5 mm in width and 9 mm in height. Data was analyzed with SPSS Program version 12 for Windows. The results showed that there were significant differences in the disposition of dental implant before and after panoramic radiography examination. As conclusion, before the installation of dental panoramic implants radiographycally, all samples had good criteria, after installation of the implants 56.7% had good criteria, 16.7% moderate and 26.7% bad criteria. Based on gender, male had higher percentage for good dental implants placement compared to female. Female had higher percentage of dental implant shifted to mesial and on the other hand, male had higher percentage of dental implant shifted to distal.